Change of Terminology as a Representation of Migration Discourse in the Media: The Case of Kazakhstan - Negizbayeva, Marlan O.; Dudinova, Yelena I.; Shyngyssova, Nazgul T.; Skripnikova, Anastasiya I.; Tassilova, Aigerim A. (The New Research of Tuva, 2025)
The article analyzes the problem of the perception of migration processes and attitudes toward migrants and migration-related terminology, using Kazakhstan as an example. In 2020, the main term used since 1997 to refer to individuals of Kazakh ethnicity who had lived outside the Republic of Kazakhstan but returned to their historical homeland after the country gained sovereignty was replaced.The case of Kazakhstan is of particular interest for studying the specifics of adaptation by both repatriates and the host society, as well as for exploring the media coverage of the state's renaming initiative. The level of media interest in the terms “kandas” and “oralman” was analyzed. It was established that the term “oralman” is familiar to citizens of Kazakhstan and Russia. There is a notable skepticism among Kazakhstanis regarding the extent to which the change of terminology will alter perceptions of repatriates. The potential for revitalization and positive transformation of migration discourse in connection with the terminological change remains unrealized. While addressing the topic, Kazakhstani journalists generally do not provide a broad representation of the diversity of opinions and discussions; more often they limit themselves to quoting official documents and refrain from employing various journalistic genres. Reporting on the change in terminology is based mainly on official information.The study revealed that audience interest in the topic was irregular; survey results indicated a positive reception of the new designation for repatriates among respondents, yet a skeptical view regarding changes in host society attitudes toward “kandas”. There were also variations in the discourse surrounding the change in terminology.
Keywords: Kazakhstan; Kazakhs; migration; kandas; media; economic policy; social development; demographic policy